TINJAUAN YURIDIS DISKRESI PEJABAT PUBLIK DALAM PENYELENGGARAAN PEMERINTAHAN - Widha Sinulingga (UIN Sunan Kalijaga Yogyakarta, 2018)
Policy (discretion) is needed to overcome rapid changes. In theapplication of discretion of public officials, it is often considered to violate thelaw and be identified as criminal. While on the other hand, this kind of policyis needed, in times of emergency, so that it makes a blunder of officials. Thispaper attempts to look at how the legal position of discretion in governmentadministration is. The results of this writing are that the legal position ofdiscretion in the administration of government is an